Critical Assessment of Cell Wall Integrity Factors Contributing to in vivo Echinocandin Tolerance and Resistance in Candida glabrata - Garcia-Rubio, Rocio; Hernandez, Rosa Y.; Clear, Alissa; Healey, Kelley R.; Shor, Erika; Perlin, David S. (Frontiers in Microbiology, 2021)
Fungal infections are on the rise, and emergence of drug-resistant Candida strains refractory to treatment is particularly alarming. Resistance to azole class antifungals, which have been extensively used worldwide for several decades, is so high in several prevalent fungal pathogens, that another drug class, the echinocandins, is now recommended as a first line antifungal treatment. However, resistance to echinocandins is also prominent, particularly in certain species, such as Candida glabrata. The echinocandins target 1,3-β-glucan synthase (GS), the enzyme responsible for producing 1,3-β-glucans, a major component of the fungal cell wall. Although echinocandins are considered fungicidal, C. glabrata exhibits echinocandin tolerance both in vitro and in vivo, where a subset of the cells survives and facilitates the emergence of echinocandin-resistant mutants, which are responsible for clinical failure. Despite this critical role of echinocandin tolerance, its mechanisms are still not well understood. Additionally, most studies of tolerance are conducted in vitro and are thus not able to recapitulate the fungal-host interaction. In this study we focused on the role of cell wall integrity factors in echinocandin tolerance in C. glabrata. We identified three genes involved in the maintenance of cell wall integrity – YPS1, YPK2, and SLT2 – that promote echinocandin tolerance both in vitro and in a mouse model of gastrointestinal (GI) colonization. In particular, we show that mice colonized with strains carrying deletions of these genes were more effectively sterilized by daily caspofungin treatment relative to mice colonized with the wild-type parental strain. Furthermore, consistent with a role of tolerant cells serving as a reservoir for generating resistant mutations, a reduction in tolerance was associated with a reduction in the emergence of resistant strains. Finally, reduced susceptibility in these strains was due both to the well described FKS-dependent mechanisms and as yet unknown, FKS-independent mechanisms. Together, these results shed light on the importance of cell wall integrity maintenance in echinocandin tolerance and emergence of resistance and lay the foundation for future studies of the factors described herein.